2019
DOI: 10.1027/1864-9335/a000387
|View full text |Cite
|
Sign up to set email alerts
|

Does Physical Warmth Prime Social Warmth?

Abstract: Is there a psychological link between physical and social warmth? The Williams and Bargh (2008) coffee study is one data point among many that bear on this question. Since its publication there has been a surge of further research on the association between physical and social warmth, especially in neuroscience and medical science. As a result, there is now an array of evidence relevant to (1) the reality of the physical-social warmth pathway and (2) its possible anatomical location and neurochemical mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…Despite its recent controversy in the social psychological literature (Chabris et al, 2019; Lynott et al, 2014; cf. Bargh & Melnikoff, 2019), these results are consistent with previous findings from the animal and human literature that show selective effects of physical warmth on social connection. In addition, they emphasize the importance of physical warmth over other less-warm temperatures for pro-social behavior (e.g., Hofer, 1973).…”
Section: Discussionsupporting
confidence: 92%
“…Despite its recent controversy in the social psychological literature (Chabris et al, 2019; Lynott et al, 2014; cf. Bargh & Melnikoff, 2019), these results are consistent with previous findings from the animal and human literature that show selective effects of physical warmth on social connection. In addition, they emphasize the importance of physical warmth over other less-warm temperatures for pro-social behavior (e.g., Hofer, 1973).…”
Section: Discussionsupporting
confidence: 92%
“… Schilder et al (2015) conducted a direct replication study of IJzerman and Semin (2009) and obtained similar results. Bargh and Melninkoff (2019) reanalyzed the data from a study that showed a failed replication ( Chabris et al, 2019 ) and found a trend similar to that of the original study. As such, the question of reproducibility remains wide open.…”
Section: Introductionmentioning
confidence: 81%
“…Bargh and Melnikoff (2019 )
So why did Chabris et al. (2019) not replicate Williams and Bargh (2008)?
…”
Section: Replication As a Dramatic Counter‐realitymentioning
confidence: 99%
“…OSC used a benchmark that did not take into account the multiple sources of error in their data, used a relatively low-powered design that demonstrably underestimates the true rate of replication, and permitted considerable infidelities that almost certainly biased their replication studies toward failure. As a result, OSC seriously underestimated the reproducibility of psychological science (p. 1037) Bargh and Melnikoff (2019) So why did Chabris et al ( 2019) not replicate Williams and Bargh (2008)? One possible answer has to do with the temperature of the coffee that participants held.…”
Section: Replication As a Dramatic Counter-realitymentioning
confidence: 99%